(untitled) (Research, Society and Development, 2021)
Cost and schedule escalation in large projects are a historical problem observed worldwide. In Brazil, this problem is recurrent in public sector works. Disruptive innovations such as Building Information Modeling (BIM) come as a solution, but it is only part of the improvement process and their synergy with other techniques such as Lean Construction can result in significant improvements in the construction industry’s performance. Therefore, this article aims to compare the implementation of BIM and identify the benefits achieved. To this end, a literature review was added to a documentary research to identify the strategies implemented by the United Kingdom and Brazil as well as the benefits achieved.